The time of recognition: a time-critical theory of social misrecognition in welfare societies - Gottfried Schweiger (Frontiers in Sociology)
This paper analyzes recognition as a temporal phenomenon. It seeks to better understand how the temporality of recognition—that is, when it is demanded, received, and given, and for how long—is structured in modern societies, and what the consequences are when these temporal structures erode or collapse. To this end, the paper focuses on two social processes: poverty and the precarization of work. It argues that both are better understood through the lens of the temporal dimension of recognition—or more precisely, the temporal dimension of non-recognition and misrecognition. This perspective reveals that poverty and precarization are temporally extended forms of non-recognition. It becomes clear that the timing of these experiences within a person’s life course, their duration, and the temporal regimes established by welfare states all play a crucial role. These regimes often exclude and disadvantage those affected, reinforcing their marginalization over time.